(untitled) - Ka, Ho Mok (Singapore, 2008)
In the last two decades, the number of children enrolling in school in the Asia and the Pacific region has steady increase. The recent crise have further weakened the position of these socially disadvantaged group to get access to education.
Keywords: Education,Education,Educational innovations,Giáo dục,Giáo dục,Đổi mới giáo dục; Statistics,Finance,Tài chính,Thống kê; Asia,Asia,Asia,Châu Á,Châu Á,Châu Á